2015
DOI: 10.1371/journal.pgen.1004814
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Aggregates Promote De Novo Prion Appearance via More than One Mechanism

Abstract: Prions are self-perpetuating conformational variants of particular proteins. In yeast, prions cause heritable phenotypic traits. Most known yeast prions contain a glutamine (Q)/asparagine (N)-rich region in their prion domains. [PSI+], the prion form of Sup35, appears de novo at dramatically enhanced rates following transient overproduction of Sup35 in the presence of [PIN+], the prion form of Rnq1. Here, we establish the temporal de novo appearance of Sup35 aggregates during such overexpression in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 132 publications
0
60
0
Order By: Relevance
“…It has no restrictions on subcellular localization, solubility, or size of the assemblies, thereby mitigating false-negatives and false-positives. In contrast, existing high-throughput assays for protein aggregation report on large puncta (Narayanaswamy et al, 2009;Noree et al, 2010;Pereira et al, 2018;Ramdzan et al, 2012) , inactivation of fusion partners (Alberti et al, 2009;Morell et al, 2011;Newby et al, 2017;Waldo et al, 1999;Zhao et al, 2016) , require restrictive subcellular localization (Sivanathan and Hochschild, 2013) , and/or necessitate expression from dual constructs (Arslan et al, 2015;Blakeley et al, 2012;Cabantous et al, 2013;Shyu and Hu, 2008) . Most importantly, DAmFRET simultaneously reports total protein concentration, and thereby the concentration-dependence of self-assembly, in every single sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has no restrictions on subcellular localization, solubility, or size of the assemblies, thereby mitigating false-negatives and false-positives. In contrast, existing high-throughput assays for protein aggregation report on large puncta (Narayanaswamy et al, 2009;Noree et al, 2010;Pereira et al, 2018;Ramdzan et al, 2012) , inactivation of fusion partners (Alberti et al, 2009;Morell et al, 2011;Newby et al, 2017;Waldo et al, 1999;Zhao et al, 2016) , require restrictive subcellular localization (Sivanathan and Hochschild, 2013) , and/or necessitate expression from dual constructs (Arslan et al, 2015;Blakeley et al, 2012;Cabantous et al, 2013;Shyu and Hu, 2008) . Most importantly, DAmFRET simultaneously reports total protein concentration, and thereby the concentration-dependence of self-assembly, in every single sample.…”
Section: Discussionmentioning
confidence: 97%
“…Rnq1 prions, for example, enable the formation of Sup35 and Ure2 prions (Derkatch et al, 2001) . The extent to which other prion proteins share this dependence, and its molecular underpinnings, remain unclear (Arslan et al, 2015;Keefer et al, 2017;Suzuki et al, 2012) .…”
Section: Nucleation Barriers Govern Amyloid "Cross-seeding"mentioning
confidence: 99%
“…Once we confirmed that the variability observed in act1-122 mutants was not due to unforeseen suppression defects, we postulated that the [PIN + ] prion could be changed in these mutants. The cross-seeding model suggests that [PIN + ] increases [PSI + ] induction through heterologous cross seeding of new Sup35p aggregates (Derkatch et al, 2004;Arslan et al, 2015). Therefore, changes in [PIN + ] could result in changes in [PSI + ] induction in act1-122 mutants.…”
Section: [Pin + ] Can Be Destabilized In Act1-122 Mutantsmentioning
confidence: 99%
“…The visualization of newly formed aggregates during the prion induction process is mediated through the fusion of a fluorescent marker to the Sup35p prion domain (Sup35PrD-GFP; Zhou et al, 2001). Overexpression of Sup35PrD-GFP leads to the appearance of small, transient "early foci" that assemble into cytosolic ring or dot aggregates (Arslan et al, 2015;Sharma et al, 2017). Micromanipulation of either ring or dot containing cells gives rise to future generations that contain [PSI + ] (Ganusova et al, 2006;Sharma et al, 2017), indicating that cells containing these newly formed aggregates are precursors to [PSI + ].…”
Section: Introductionmentioning
confidence: 99%
“…25,52,57 However, an interaction between these proteins is of transient nature and is observed only at early stages of the induction process, while persistent coaggregates are not formed and stable colocalization is not reported. [58][59][60] It was shown that different amylodogenic proteins can be assembled in the form of ordered aggregates in the yeast quality control deposits, such as insoluble protein deposit, IPOD, 61 or aggresome 62,63 (that may represent a version of IPOD with a somewhat different intracellular location). However, the very distantly related Sup35 protein from the other yeast genera, Pichia does not colocalize with the preexisting S. cerevisiae Sup35 prion, 50 suggesting that in case of more closely related proteins, colocalization might be not simply a result of co-sequestration into IPOD.…”
Section: At Whichmentioning
confidence: 99%